2005
DOI: 10.1038/sj.mp.4001745
|View full text |Cite
|
Sign up to set email alerts
|

Psychosis and the genetic spectrum of bipolar disorder: evidence from linkage analysis

Abstract: the present study may not have been large enough to exclude involvement of a polymorphism with weak effect. Furthermore, in our study sample, to detect the difference between 93/196 and 103/196 with power 0.5, the minimum sample size should be 778. Similarly, to detect the difference between 237/461 and 224/461 in the sample from three Chinese studies with power 0.5, the minimum sample size should be 2487. If a higher power is desired, say, 0.8, then the required minimum sample size would be much greater than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
1
3
0
Order By: Relevance
“…We previously reported a significant bipolar locus at 8q24 in a cohort of persons of Latin American ancestry (Gonzalez et al, ), which replicates findings from other BD linkage studies (Avramopoulos et al, ; Cheng et al, ; Cichon et al, ; McInnis et al, ; McQueen et al, ; Park et al, ). The present fine mapping of markers in this region pinpoint one specific gene that has evidence of significant association in this sample of persons responsible for the original linkage finding.…”
Section: Discussionsupporting
confidence: 83%
“…We previously reported a significant bipolar locus at 8q24 in a cohort of persons of Latin American ancestry (Gonzalez et al, ), which replicates findings from other BD linkage studies (Avramopoulos et al, ; Cheng et al, ; Cichon et al, ; McInnis et al, ; McQueen et al, ; Park et al, ). The present fine mapping of markers in this region pinpoint one specific gene that has evidence of significant association in this sample of persons responsible for the original linkage finding.…”
Section: Discussionsupporting
confidence: 83%
“…However, we cannot determine from this analysis whether the differences found between child and adolescent age of onset subgroups are an independent effect of age when illness begins, or are affected by susceptibility genes that confer early age of onset. However, interestingly, studies of adult BP have noted heterogeneity of linkage associated with psychotic features and anxiety (38), as well as familiality of a range of phenotypic characteristics in families with BP (39). Whatever the reason for these differences, it will be crucial for ongoing molecular, genetic, neuroimaging, and treatment studies to take into account the age of BP onset, maturational effects, and the presence of comorbid disorders and differential exposure to stress to fully explicate research findings.…”
Section: Discussionmentioning
confidence: 99%
“…FKBP5 has not been identified as a risk gene by genome-wide association studies (GWAS). However, chromosome 6, which houses the FKBP5 gene, was associated with psychosis by GWAS . Instead, candidate gene studies, which use a hypothesis driven approach, have identified common FKBP5 single nucleotide polymorphisms (SNPs) that combine with environmental factors to increase risk for multiple neuropsychiatric disorders. In PTSD, multiple studies have reported that FKBP5 SNPs combine with early life stress to increase risk; however, GWAS studies have not supported this .…”
mentioning
confidence: 99%